Perfil de los pacientes atendidos en la clínica de implantodoncia de las Facultades Adamantinenses Integradas (FAI) - Ferreira, Jean Paulo Rodolfo [UNESP]; Araújo, Paula Caetano [UNESP]; Saliba, Marcos Tadeu Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2015)
Objective: The aim of this study was to identify the profile of patients treated at the Implantology clinic of the Integrated Schools of Adamantina-FAI, Adamantina-SP, Brazil, through analysis of medical records, appliance of questionnaire and execution of clinical examination. Material and methods: The sample universe of this study consisted of 96 medical records and 96 patients seen over the 9 years of FAI’s experience in the discipline of Implantology. The results were analyzed in the IBM SPSS StatisticsVersion 19 program and the Fisher’s exact and chi-square tests were also applied. Discussion / Results: It was observed that 53.97 % of the participants have lost their natural teeth due to caries. The type of implant prosthesis most used was the fixed denture (88 %). It is also important to note that almost all of the patients had no loss of implant, and these individuals were mostly aged less than or equal to 49 years for women (73.8 %) and greater than or equal to 50 years for men (61.8 %). In relation to the quantity of implant elements, the use of 2 implants or less was the most common rehabilitation for both sexes. Another important observation is that only 15.8 % of the participants have the habit of smoking. Conclusion: Thus, the profile of the treated patient at the Implantology clinic of FAI, is mostly women, healthy, aged less than 49 years old, non-smoking, which rehabilitated 1 or 2 teeth, with almost no incidence of implant lost and who opted for fixed denture supported by the implants.
Perfil dos pacientes atendidos na clínica de Implantodontia das Faculdades Adamantinenses Integradas (FAI)
Profile of the treated patients at the implantology clinic of Integrated Schools of Adamantina (FAI)
Keywords: Dental; Dental implantation; Education; Health services; Higher; Patient care